Pengelolaan Evaluasi Pembelajaran Kurikulum 2013 Di SD Negeri 01 Karanganyar - Sholeh, Muhammad; , Prof. Dr. Sutama, M.Pd; , Dr. Sumardi, M.Si (2016)
Objective: (1) Describe the management planning, implementation, evaluation, and follow-up in 2013 affective learning curriculum. (2) Describe the management planning, implementation, evaluation, and follow-up of cognitive aspects of learning the curriculum in 2013. (3) Describe the management planning, implementation, evaluation, and follow-up learning curriculum 2013 psychomotor aspect. Qualitative research. The place of research in SD Negeri 01 Karanganyar. When the study in January 2016 to June 2016. The research subjects principals, teachers and students of SD Negeri 01 Karanganyar. Data collection techniques of interview, observation and documentation. Validity of data with triangulation techniques and triangulation of sources. Data were analyzed using an interactive analysis, the process of data reduction, data presentation and conclusion. RESULTS: (1) Management of affective aspects of learning evaluation, carried out using an attitude evaluation, self evaluation, evaluation of journal notes between friends and teachers as basis for grading and descriptions on rapot learners. (2) Management of the cognitive aspects of learning evaluation conducted by the evaluation of written, oral and assignments are conducted at the end of learning to know the material that is acceptable learners. The results of the evaluation of the cognitive aspects of the basis for the grading and the description on rapot learners (3) Management evaluation of learning psychomotor aspect done by providing performance evaluation, project and portfolio performed after learning and nothing to do at home either individually or in groups, the evaluation results the basis in the scoring and descriptions on rapot learners.